Welfare implications of power rationing: An application to Germany - Lars Wenzel; André Wolf (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2014)
This study analyzes the economic consequences of power rationing at the level of German counties. Based on a common production function approach, it estimates the costs of power outages for firms and households in all counties and uses these estimates to derive hypothetical rationing plans for the scenario of a country-wide shortage of power supply. Rationing plans are introduced according to several criteria: a random-based approach, a criterion of total cost minimization, a criterion minimizing costs of the most affected region as well as a criterion minimizing the number of people affected. The implementation of each criterion is simulated for different times of the day. The spatial patterns of rationing prove to be heterogeneous. Estimated cost structures differ to some extent as well. The results are discussed with regard to enforceability in the context of the German energy transition. – – Diese Studie untersucht die ökonomischen Implikationen von Stromrationierung auf Ebene der deutschen Kreise. Basierend auf einem einfachen Produktionsfunktionsansatz werden Stromausfallkosten auf Seiten von Unternehmen und Haushalten geschätzt. Diese Schätzwerte werden zur Ermittlung hypothetischer Rationierungspläne auf Grundlage eines bundesweiten Szenarios von Stromknappheit herangezogen. Den Plänen werden dabei verschiedene Kriterien zugrunde gelegt: ein zufallsbasierter Ansatz, ein Kriterium zur Minimierung der Gesamtkosten, ein Kriterium zur Schadensminimierung in den am stärksten betroffenen Kreisen sowie ein Kriterium zur Minimierung der Anzahl an betroffenen Einwohnern. Die Implementierung der hieraus abgeleiteten Pläne wird für verschiedene Tageszeiten simuliert. Dabei erweisen sich die räumlichen Muster der Rationierung und die daraus resultierenden Kostenverteilungen als relativ heterogen. Die Ergebnisse werden im Hinblick auf ihre Umsetzbarkeit vor dem Hintergrund der deutschen Energiewende diskutiert.
Keywords: 330